Molecular Patterns of MEFV Gene Mutations in Egyptian Patients with Familial Mediterranean Fever: A Retrospective Cohort Study - Amal R. Mansour; Ayman El-Shayeb; Nihal El Habachi; Mohamad A. Khodair; Doaa Elwazzan; Nermeen Abdeen; Marwa Said; Riham Ebaid; Noha ElShahawy; Amr Seif; Nadia Zaki (International Journal of Inflammation)
Background. Familial Mediterranean Fever (FMF) is a hereditary autosomal recessive disease which is mainly seen in the Turks, Armenians, Arabs, and Jews. It is characterized by recurrent episodes of fever, polyserositis, and rash. MEFV gene, encoding pyrin protein, is located on the short arm of chromosome 16. FMF is associated with a broad mutational spectrum in this gene. Certain mutations are more common in particular ethnic groups. To date, different mutations of MEFV were observed in studies carried out in different regions worldwide. However, most of these studies did not extensively investigate the Egyptian population, in spite of the high prevalence of FMF in this geographical region. Aim. To identify the frequency of MEFV gene mutations among the patients who presented with FMF like symptoms and, to characterize the different genetic mutations and their association with increased Amyloid A among Egyptian patients. Methods. FMF Strip Assay (Vienna Lab Diagnostics, Vienna, Austria) was used. This test is based on reverse hybridization of biotinylated PCR products on immobilized oligonucleotides for mutations and controls in a parallel array of allele-specific oligonucleotides. Results. Among the 1387 patients presenting with signs and symptoms suggestive of FMF, 793 (57.2%) were of undefined mutations, whereas 594 had MEFV gene mutations. 363 patients (26.2%) were heterozygous mutants, 175 patients (12.6%) were compound heterozygous mutants, and 56 patients (4%) were homozygous mutants. The most commonly encountered gene mutations in heterozygous and homozygous groups were E148Q (38.6%), M694I (18.1%), and V726A (15.8%). The most commonly encountered gene mutations in the compound heterozygous groups were E148Q+M694I observed in 20.6% of the patients, followed by M694I+V726A and M6801+V726A found in 18.9% and 11.4 %, respectively. The most commonly encountered gene mutation associated with abdominal pain, fever, and high serum Amyloid A was E148Q allele (37.5%). Conclusions. Unlike all previous publications, E148Q allele was found to be the most frequent in the studied patients. Moreover, this allele was associated with increased Amyloid A. 793 patients were free of the 12 studied Mediterranean mutations, which implies the necessity to perform future sequencing studies to reveal other mutations.